(3CMcGe GdfSGA heG jNUgfs - (3eMeO Hf eMeO Hf GdfYeGf Hf YHO GdSdGe GdYcHQqj, CHh YHO Gddg, GdeajO, hjYQa HGHf GdeYde , J (B413 (3g`s ((3eMeO Hf GdTjN WGgQ GdSeGhi s)
(3ChdgG (B:s
(3hHYO aEfi LeYJ dGKGQ GdSjOI GdLdjdI GdaGVdI BOGe Gddg GYRGRgG s
(3BNQgG (B:s
(3hOaf GdejJ ai GdJQGH CaVd ef Oafg ai GdJhGHjJ HPdc LGFJ GdSfI s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B21 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B306s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B1 - (3U (B37s
Keywords: (3abg GdePGgH GdCNQis